Development of Novel Arginase Inhibitors for Therapy of Endothelial Dysfunction - Steppan, Jochen; Nyhan, Daniel; Berkowitz, Dan (Frontiers in Immunology, 2013)
Endothelial dysfunction and resulting vascular pathology have been identified as an early hallmark of multiple diseases, including diabetes mellitus. One of the major contributors to endothelial dysfunction is a decrease in nitric oxide (NO) bioavailability, impaired NO signaling and an increase in the amount of reactive oxygen species (ROS). In the endothelium NO is produced by eNOS (endothelial nitric oxide synthase), for which L-arginine is a substrate. Arginase, an enzyme critical in the urea cycle also metabolizes L-arginine, thereby directly competing with eNOS for their common substrate and constraining its bioavailability for eNOS, thereby compromising NO production. Arginase expression and activity is upregulated in many cardiovascular diseases including ischemia reperfusion injury, hypertension, atherosclerosis, and diabetes mellitus. More importantly, since the 1990s, specific arginase inhibitors such as N-hydroxy-guanidinium or N-hydroxy-nor-L-arginine, and boronic acid derivatives, such as, 2(S)-amino-6-boronohexanoic acid, and S-(2-boronoethyl)-L-cysteine (BEC), that can bridge the binuclear manganese cluster of arginase have been developed. These highly potent and specific inhibitors can now be used to probe arginase function and thereby modulate the redox milieu of the cell by changing the balance between NO and ROS. Inspired by this success, drug discovery programs have recently led to the identification of α-α-disubstituted amino acid based arginase inhibitors (such as (R)-2-amino-6-borono-2-(2-(piperidin-1-yl)ethyl)hexanoic acid)), that are currently under early investigation as therapeutics. Finally, some investigators concentrate on identification of plant derived compounds with arginase inhibitory capability, such as piceatannol-3'-O-β-D-glucopyranoside (PG). All of these synthesized or naturally derived small molecules may represent novel therapeutics for vascular disease particularly that associated with diabetes.